Efeito tripanocida de substâncias presentes no cajueiro ( Anacardium occidentale): uma abordagem experimental e teórica - Marinho, Márcia Machado (2020)
Endemic in 21 countries in Latin America, Chagas disease, caused by Trypanosoma cruzi, kills more people in the region each year than any other disease caused by parasites, including malaria. Northeastern Brazil is the second endemic region for Chagas disease in the country. Due to the caatinga vegetation and still very precarious human dwellings, in Ceará we find a great diversity of triatomines such as Triatoma pseudomaculata, Triatoma brasiliensis and Panstrongylus megistus, important in the transmission of the disease in the state, being a state with a high prevalence of the disease. In Brazil, only benznidazole is used for the treatment of Chagas disease, requiring an urgent search for new, more effective and safe drugs. Thus, the present work aimed to study the trypanocidal effect of substances present in the cashew tree (Anacardium occidentale) on the evolutionary forms of the Y strain of Trypanosoma cruzi, in an experimental and theoretical approach. The cashew leaf infusion and anacardic acid were evaluated on the evolutionary forms of T. cruzi, epimastigotes (24, 48 and 72 h), trypomastigotes (24 h) and amastigotes (24 h). Flow cytometry assays were also performed to evaluate the mechanisms of cell death with epimastigote forms treated with anacardic acid, with the markers 7AAD / annexin V, Rho123, H2DCFHDA and Acridine Orange. Scanning electron microscopy (MEV) was used to identify possible ultrastructural changes in epimastigote forms treated with anacardic acid. In the experimental approach, the cytotoxicity of the cashew leaf infusion evaluated in LLC-MK2 cells by the MTT method, showed that the infusion showed low cytotoxicity in the concentrations of 1800, 900 and 450 μg / mL. The concentrations that showed the greatest cytotoxic effect on epimastigotes and trypomastigotes were 225; 112.5 and 56.25 μg / mL. The infusion also had an anti-mastic effect, with a reduction (50%) in the average count of amastigotes / infected cells. As for anacardic acid, it showed a decrease of more than 50% in the number of amastigotes / 100 cells within 24 hours. As for the theoretical approach, an in silico study of anacardic acid and amentoflavone was carried out with the main pharmacological targets of T. cruzi: TcGAPDH, Cruzaína and Tripanotiona reductase. The cashew leaf infusion and anacardic acid have shown promise for the study and development of therapeutic alternatives for the treatment of Chagas disease.